Budaya Urban Muslim Kelas Menengah - Rofhani Rofhani (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2013)
This article discusses the cultural dimension is understood in the conventional sense, i.e. as beliefs, values, and a person’s lifestyle in everyday life. This article will also examine the cultural phenomenon of the modern (or even postmodern) by some regarded as an ethical culture that reduces the community's value. These conditions then led to the birth of fundamentalism that offers Islamic culture. But in its development, this solution has not quite accepted by the Muslim urban middle class, as assessed ancient cultures offer, traditional or even outmoded, but on the other hand, they also indicate negation of the Western culture which is considered to damage the image of Muslims. Therefore, this group tried to make a synthesis of culture with other cultures and offer a style that still offers a more modern Islam and not obsolete.